Glandular odontogenic cyst in a young Indian female: A rare case report with review of literature - Vishwas D Kadam; Govind R Changule; Sneha H Choudhary; Lalitkumar P Gade (Wolters Kluwer Medknow Publications, 2020)
Glandular odontogenic cyst (GOC) is a developmental odontogenic cyst of jaw bones, described in 1987 by Gardner et al. The cyst is rare in occurrence, especially in Indians, unpredictable in nature, potentially aggressive in its behavior and has a very high recurrence rate. Clinically, the age, gender, and site of occurrence of GOC as per the literature are 5th- 6th decade of life, slight male predilection and mandibular anterior region. This article presents a case of GOC in a 28-year-old female patient in the posterior mandibular region which is a rare combination of age, gender and site of occurrence for GOC.